Differential Effects of Moderate or Heavy Alcohol Consumption on Circulating Adhesion Molecule Levels - Sacanella, E.; Badía, E.; Nicolás, J. M.; Fernández-Solá, J.; Antúnez, E.; Urbano-Márquez, A.; Estruch, R. (Thrombosis and Haemostasis, 2002)
Epidemiological studies suggest that moderate but not heavy alcohol consumption provides protection against coronary heart disease. We assessed the relationship between alcohol consumption and serum levels of adhesion molecules involved in the pathogenesis of early atherosclerosis. One-hundred apparently healthy men with similar cardiovascular risk factors were divided into four groups according to ethanol intake. Moderate drinkers (20-40 g/day) showed lower serum intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) levels than abstainers (p <0.05; both), as well as lower serum ICAM-1, VCAM-1 and E-selectin levels than heavy drinkers (p = 0.01; all). The latter also showed higher serum ICAM-1 and E-selectin levels than abstainers (p <0.001; both). We conclude that moderate drinkers show a significant reduction of soluble endothelial adhesion molecule levels compared to abstainers and heavy drinkers, that may contribute to the protective effect of moderate alcohol consumption against atherosclerosis.
Keywords: VCAM-1; E-selectin; ICAM-1; alcohol consumption; atherosclerosis